When Does Beauty Pay? A Large-Scale Image-Based Appearance Analysis on Career Transitions - Malik, Nikhil; Singh, Param Vir; Srinivasan, Kannan (Information Systems Research, 2024)
When Does Beauty Pay? A Large-Scale Image Based Appearance Analysis on Career Transitions In this study, we collect up to 15 years of career histories for over 40,000 MBA graduates from top 100 MBA programs in the United States. We find that attractive MBA graduates earn at least $2,508 more in yearly salary compared with plain-looking (unattractive) MBA graduates. The attractiveness premium is even larger for top 10 percentile attractive graduates, for those with arts undergraduate majors, and those in managerial roles, nontechnical jobs, and non-IT industries. Policymakers should note that the attractiveness bias is not much smaller in size than gender bias. It is pervasive over time (in individuals in their 30s and 40s and not just 20s) and across industries. It may need a similar focus as gender or racial bias in labor markets. Companies can craft their HR trainings and procedures guided by this finding. A study of this scale is only possible using cutting-edge machine learning and generative AI methods (instead of human subjects) for large-scale data processing.